Towards a postcolonial politics of appearance: unsettling lifelong learning as a racial contract. Issue 1 (2nd January 2019) - Shan, Hongxia
ABSTRACT: In the context of flexible capitalism, lifelong learning has been posed as a pathway for individuals to accumulate skills and actualise potentials. What is overlooked, however, is that the process of accumulation and actualisation is embedded within the culture of recognition. People who are historically constructed as the anthropos, a legacy of the colonial history struggle to appear as equals vis-à-vis the gaze of the humantias . With this critique in view, I reviewed the field of immigrant and lifelong learning in relation to a postcolonial politics of appearance. I sought to understand how lifelong learning settles itself in immigrant consciousness, and how it shapes immigrant experiences in the West. My review points to three metaphors that speak of the challenges and possibilities for immigrants to appear: fixation of the Eurocentric gaze, re-credentialing as precarious investment, and lifelong learning as trans/formation. Together, these metaphors suggest that lifelong learning has conjured a racial contract, which ironically binds immigrants to the labour of learning and yet continuously suppresses their appearance. To unsettle this racial contract, borders need to be reimagined and crossed/vexed by recentring immigrants as knowing subjects.